SÍNDROME METABÓLICA: PREVALÊNCIA E ASSOCIAÇÃO COM DOENÇAS CARDIOVASCULARES EM ADULTOS - Mariana Fernandes Costa; Joyce do Valle (Universidade do Estado do Rio de Janeiro, 2012)
This study aimed to investigate the prevalence of metabolic syndrome and the association with cardiovascular disease. The patients evaluated were individuals aged 30-74 years without previous diagnosis of cardiovascular disease, treated in the Nutrition clinic of the municipal hospital in Niterói city for seven months. The metabolic syndrome happens with the combination of three or more conditions such as high blood pressure, high blood glucose, high plasma triglycerides, low HDL cholesterol, and high waist circumference. Anthropometric and biochemical variables were collected. The estimate of cardiovascular risk in ten years was obtained by the Framingham score. Among the 36 patients, 80.56% were women. The frequency of metabolic syndrome in women was 89.66% and 42.86% in men; 91.67% had hypertension; 77.78% were diabetic type II; 86.11% had overweight. High waist circumference, high plasma triglycerides and high blood glucose were more prevalent in women; hypertension and low HDL cholesterol were more prevalent in men. The women had presented in average 14,97 ± 8.39% of cardiovascular risk, and men, 22,00 ± 17,03%. The correlation between metabolic syndrome and cardiovascular risk was statistically significant. The abdominal skinfold is only associated with anthropometric variables. The metabolic syndrome was present in 80.56% of the individuals, directly related to high cardiovascular risk. The results indicate the importance of preventive treatment and reduction of risk factors for cardiovascular disease, as well as the recognition of individuals with metabolic syndrome.